Peningkatan Produktivitas UMKM Melalui Pemberdayaan Reseller di PT. Keloria Moringa Jaya - Dewi Shinta Wulandari Lubis; Dina Octavia; Soraya Grabiella Dinamika; Ade Rahma Ayu (Lembaga Penelitian dan Pengabdian Masyarakat STIE Eka Prasetya, 2022)
MSME is a sector that must be of concern to the Republic of Indonesia because it has an important role in the economy of the Indonesian people, one of which is being able to create jobs and increase people's income. Seeing the important role of MSMEs, it is necessary to conduct training to help MSMEs overcome various existing problems from all aspects. One thing that can be done is the Community Service Training (PKM) activity entitled 'Increasing MSME Productivity Through Reseller Empowerment at PT. Keloria Moringa Jaya' where the participants in this activity consisted of MSME actors and workers at PT Keloria Moringa Jaya. The methods given are presentations, discussions, case studies, and final evaluations. This activity aims to provide increased knowledge in increasing productivity by empowering resellers to increase their sales and will increase their income. The results of this activity concluded that this activity really helped participants in increasing their understanding and awareness of reseller empowerment.